Preparation and properties of rapeseed straw based porous carbon materials - Yan, Sha; Hu, Siyu; Yang, Qinyu; Guo, TIng; Zhao, Xinxin; Wang, Meng; Zhao, Zuoping (International Journal of Agricultural and Biological Engineering, 2024)
The conversion of rapeseed straw into biochar not only effectively mitigates pollution from traditional straw burning but also aligns with China’s sustainable agricultural development goals. A significant quantity of rapeseed stalks is frequently burned in fields, leading to severe air pollution characterized by black smoke and residue, resulting in a substantial waste of straw resources. To address this issue, rapeseed straw form Nanchi Village, Puzhen Town, Hanzhong City, Shaanxi Province, China was utilized as a precursor and KOH was employed as an activator to produce porous activated carbon by pyrolysis. Scanning electron microscopy (SEM), elemental analyzer, infrared spectroscopy, specific surface area analysis, and other instruments were employed to characterize the porous activated carbon produced under various temperature gradients and activator concentrations. The microelement composition, structure, specific surface area, and pore size of biochar produced under varying conditions were analyzed to determine the optimal preparation parameters. Furthermore, the adsorption efficiency for tetracycline in wastewater was evaluated using a three-factor, three-level orthogonal experimental design. The results showed that the interior of the activated carbon was porous, while the exterior contained oxygenated functional groups that facilitated the adsorption of nitrogen, phosphorus, and other elements. The optimal carbonization temperature and KOH concentration for activated carbon were determined to be 400°C and 0.5, respectively. The optimal adsorption conditions were identified as pH value of 7, an initial tetracycline concentration of 30 mg/L, a biochar dosage of 0.2 g, an adsorption time of 60 min, and a removal rate of 98.53%. The factors influencing the adsorption of tetracycline onto rapeseed straw biochar were ranked as initial tetracycline concentration>adsorption reaction time>biochar dasage. The findings will provide valuable references for research on biochar performance and the treatment of tetracycline contamination in water. Keywords: rapeseed straw, biochar, preparation, characterization, adsorptionDOI: 10.25165/j.ijabe.20241705.8882Citation: Yan S, Hu S Y, Yang Q Y, Guo T, ZHao X X, Wang M, et al. Preparation and properties of rapeseed straw based porous carbon materials. Int J Agric & Biol Eng, 2024; 17(5): 120-127.